The Influence of Elementary School Teachers' Community in the Use of Digital Media on Self-Efficacy and Information and Communication Technology Skills in The Cut Nyak Dien Cluster, Cilacap Selatan - Titin Sumarni (Proceedings Series on Social Sciences & Humanities, 2025)
This study was done to know the effect of elementary school teachers' Community in the use of digital media on self-efficacy and ICT skills due to the importance that teachers should have ICT skills in learning activities in the classroom. Digital media used are Ms. Word. Excel and Canva. The purpose of this study was to determine the effect of elementary school teachers' community in the use of digital media on self-efficacy and ICT skills. This study used survey research by collecting data or information about a large population using a relatively small sample. According to the results of the study on the influence of teachers in the use of digital media on self-efficacy and ICT skills in the Cut Nyak Dien Cluster, Cilacap Selatan increased the self-efficacy and ability of the teachers for learning activities in their classrooms. This Study find that 1) 100% of respondents experienced an increase in both dependent variables, 2) Self-efficacy increased by an average of 43.1% after the training, 3) ICT skills increased by an average of 52.0% after training, 4) There were no respondents who experienced a decrease in both aspects. This is great, because the use of digital media really influences student learning outcomes. Therefore, this training should always be carried out continuously so that teachers' self-efficacy keeps increasing and ICT skills become improved.